Disciplinary Management in Public Primary Schools and Teachers Job Effectiveness in Yakurr Local Government Area, Cross River State, Nigeria - Valentine J, Owan; Bassey, Ekpe Mercy (World Journal of Vocational Education and Training, 2019)
The study examined disciplinary management in public primary schools and teachers’ job effectiveness in Yakurr Local Government Area, Cross River State. Three null hypotheses were formulated accordingly to guide the study. The study adopted a descriptive survey research design. Census technique was adopted in selecting the entire population of 98 primary school managers which comprised of 49 head teachers and 49 deputy head teachers across 49 public primary schools available in the area. A questionnaire tagged: "Disciplinary Control in Public Primary Schools and Teachers’ Job Effectiveness Questionnaire (DCPPSTJEQ)" designed and administered by the researcher was used as an instrument for data collection. The null hypotheses were all tested at .05 level of significance using Pearson Product Moment Correlation Analysis. Findings from the study revealed that warning, suspension, and dismissal have significant relationships respectively, to primary school teachers’ job effectiveness. Based on the findings of this study, it was recommended among others that; there should be fairness in the administration of suspension to all teachers through well-documented procedures.